On the Strong Solutions and the Structural Stability of the g-Bénard Problem. (12th March 2018) - Özlük, Muharrem; Kaya, Meryem
ABSTRACT: In this paper, we study a type of modified Boussinesq equations which is called g-Bénard problem. We show the existence and uniqueness of strong solutions of the problem in two dimensions, and then, we investigate the continuous dependence of the solutions on the viscosity parameter.